Increasing of Students Motivation and English Speaking Skill Using Word Guessing Game at Social Class Grade XI in Senior High School of 2 Bandar Lampung, in the Academic Year of 2010/2011 - . Suranto (LINGUISTIKA, 2011)
The objective of the research was to describe how to make lesson plan, implementation, evaluation system, reflect the word guessing game for increasing motivation and students speaking skill.The study used the model of Classroom Action Research. It was conducted in three cycles. The first cycle was a big group discussion (classical), second cycle was a small group discussion, third cycle was a pair. To obtain the research data, it was used some instruments, A13KG 1, the observation of students activities, students motivation , evaluation system and students speaking skill test.The conclusions of the study are: 1) there were improvement in lesson plan quality, the first cycle was score 2,80 (poor category ), second cycle was score 3,80 (average, )third cycle was score 4,20 (good ), 2) at the first cycle, student was active 55% in social one and in social two 68%, second cycle, in social one increased 80% and in social two 82%, third cycle, in social one increased 100% and social two 100% , 3) evaluation system of the students speaking skill was implemented by pre-test and post- test, pre-test validity was 0,89, reliability was 0,91, post-test validity was 0,84, reliability was 0,80, 4) students motivation in social one average 25%, high motivation 41% and average 40%, high motivation 59% in social two, second cycle increased average motivation in social one 15%, high motivation 75% and social two average motivation 18% high motivation 77%, third cycle increased average motivation 22%, high motivation 77%,5) students speaking skill in social one increased 35% (40% became 75%) and in social two 36,5% (45,5% became 82%).